Salivary Interleukin-6 Level in Iraqi Patients with Oral Lichen Planus receiving Platelet-Rich Plasma Injections - Asal, Haider A.; Diajil, Ameena Ryhan; Al-Asady, Furqan (AL-Kindy College Medical Journal, 2023)
Background: Interleukin-6 (IL-6) is a cytokine that has several functions, including stimulating growth and inhibiting cell death. It has the potential to operate as a biomarker for the accurate prediction of disease severity and activity, platelets-rich plasma was used in the treatment of oral lichen planus and can change the salivary IL-6 level.Objectives: To study the clinical outcome of intralesional platelets-rich plasma in patients with oral lichen planus and to measure salivary IL-6 levels before and after the treatment with platelets-rich plasma were the aims of this study.Subjects and Methods: In this clinical trial, for each patient a standardized case sheet was filled including demography, social, medical, and medication history. Before receiving, each patient was examined for phenotype, color, size, and site of oral lichen planus lesions. Patient's salivary samples were taken between 8 and 11 a.m. Three to four milliliters of saliva was obtained from each patient. The ELISA kit for IL-6 using sandwich-ELISA technique, to measure salivary IL-6 before and after PRP injections.Results: Thirteen oral lichen planus patients were took part in this study, six males (46.2%) and seven females (53.8%). The patients were between 32 and 91 years of age, with a mean age of 60.2(±13.9) years. All symptomatic and most of the hyperemic ones showed improvement after PRP injections, while the size of the lesions was resistant to change. Mean salivary IL-6 was 44.27 pg/mL (±43.24) before PRP injections and (69.74±59.86 pg/mL) after PRP injections. No significant difference was found, however IL-6 was higher after PRP injections. In relation to color changes after PRP, there was a significant changes in IL-6 level compared with that before PRP injections. Similarly, a significant relation was found between IL-6 level and signs and symptoms; pain and burning sensation. No association was found in salivary IL-6 level in relation to lesion phenotype, size, and location.Conclusion: All symptomatic OLP lesions that were treated with intralesional PRP responded very well, similarly almost all hyperemic lesions turned into normal mucosal color after completing the course of treatment. The majority of OLP lesions showed an increased salivary IL-6 levels after PRP treatment.